2017
DOI: 10.1038/ncomms14763
|View full text |Cite
|
Sign up to set email alerts
|

The structure of Zika virus NS5 reveals a conserved domain conformation

Abstract: The recent outbreak of Zika virus (ZIKV) has imposed a serious threat to public health. Here we report the crystal structure of the ZIKV NS5 protein in complex with S-adenosyl-L-homocysteine, in which the tandem methyltransferase (MTase) and RNA-dependent RNA polymerase (RdRp) domains stack into one of the two alternative conformations of flavivirus NS5 proteins. The activity of this NS5 protein is verified through a de novo RdRp assay on a subgenomic ZIKV RNA template. Importantly, our structural analysis lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 29 publications
4
83
0
Order By: Relevance
“…Tertiary structure of ZIKV-NS5 reveals an N-terminal MTase domain, situated at the top of Cterminal RdRp domain. A Rossmann fold dominates the MTase domain with a seven stranded β-sheet, between two α-helices 21 . To find the potential inhibitors, a total of 2035 phytochemicals were analysed for in this study for their inhibitory potential against ZIKV-NS5.…”
Section: Resultsmentioning
confidence: 99%
“…Tertiary structure of ZIKV-NS5 reveals an N-terminal MTase domain, situated at the top of Cterminal RdRp domain. A Rossmann fold dominates the MTase domain with a seven stranded β-sheet, between two α-helices 21 . To find the potential inhibitors, a total of 2035 phytochemicals were analysed for in this study for their inhibitory potential against ZIKV-NS5.…”
Section: Resultsmentioning
confidence: 99%
“…The study suggests that: (i) NS5 recruits SIAH2 for the ubiquitination-dependent degradation of STAT2; and (ii) the NS5 amino acid residues involved in interaction with SIAH2 and/or STAT2 were found to be conserved across related flaviviruses [42]. Another structural study of ZIKV NS5 indicated that the smallmolecule inhibitor-binding site of DENV3 NS5 is structurally conserved in ZIKV NS5, indicating a potential mechanism for functional inhibition of ZIKV NS5 [43]. In principle, small molecules interfering with the function of any ZIKV viral proteins have potential in restricting virus replication and preventing the progress of ZIKV-infection-related pathogenesis and diseases.…”
Section: Viral Proteins As Drug Targetsmentioning
confidence: 95%
“…The catalytic site is positioned at the intersection of two tunnels; one provides access to the active site for the single-stranded RNA template and the second tunnel allows entry of NTPs at one end and exit of the nascent double-stranded RNA at the other end 84,85 . Recently, the crystal structures of the ZIKV full-length NS5 protein 86,87 and RdRp 88 were reported.…”
Section: Ns5 Polymerase Inhibitorsmentioning
confidence: 99%